2014
DOI: 10.9734/air/2014/10315
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sexuality Education on Inappropriate Sexual Behaviours among Secondary School Students

Abstract: The study investigated the influence of parents, teachers and government attitudes towards sexuality education on inappropriate sexual behaviours of secondary school students. One hundred and twenty-five senior secondary school students were used for the study. Related literatures that discussed issues of Sexuality education, sexual behaviours among students were used as theoretical basis for the study. Three research questions and hypotheses were developed for the study. A research instrument titled "Sexualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Sexuality is a natural part of life and it is defined as the very essence of one’s humanity which includes one’s self–image, gender, physical looks and ability to reproduce [ 1 ]. Human sexuality is concerned with the way people experience and express themselves as sexual beings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexuality is a natural part of life and it is defined as the very essence of one’s humanity which includes one’s self–image, gender, physical looks and ability to reproduce [ 1 ]. Human sexuality is concerned with the way people experience and express themselves as sexual beings.…”
Section: Introductionmentioning
confidence: 99%
“…Human sexuality is concerned with the way people experience and express themselves as sexual beings. On the other hand, sex education involves the process of acquiring knowledge and making up beliefs, values, and attitudes about intimacy, relationships, and identity [ 1 ]. Due to the influence of religion, cultural background and norms of many African societies especially parents most times find it difficult to teach their adolescents about sex, with the mind that such matter should not be discussed at home and that the child does not need such information until he or she is ready for marriage [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mohammed (2012) identified five types of sexual behaviours found among secondary school students and these include kissing, breast and genital fondling, embracing, holding of arms and sexual intercourse. Obiunu (2014) equally observed that the incidence of inappropriate sexual behaviours is on the increase among secondary school adolescent students in Delta State and that these negative behaviour manifest in different ways which usually involve a strong desire to experiment on sexual activities. Much of this sexual behaviour appear to be in aberration to values cherished by the Nigerian society.…”
Section: Introductionmentioning
confidence: 99%
“…Newspapers today repeatedly give reports of unusual sexual behaviour such as rape, lesbianism, incest, homosexuality and teenage pregnancies. Other examples according to Aji and Aji, Ifeadike, Emelumadu, Ubajaka, Nwabueze and Azuike (2013), Obiunu (2014), Agbede, Kio and Ajetunmobi (2016) include unsafe or unprotected sex, multiple sex partners, masturbation, sexual harassment and sexual bullying. These negative behaviours no doubt are at variance with most African cultures.…”
Section: Introductionmentioning
confidence: 99%